Pengaruh Gender Diversity, Expertise Diversity, CEO Duality dan Board Size terhadap Prediksi Financial Distress - Rexy Regina Dwi Chantika Rosadi; Vaya Julliana Dillak (Universitas Batanghari Jambi, 2023)
This study aims to determine the effect of gender diversity, expertise diversity, CEO duality, and board size on predictions of financial distress in retail and primary goods sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The sampling technique in this study was by purposive sampling method or as many as nine companies with 45 annual report data. However, there is one data outlier, so only 44 annual reports are used as research samples. The research method used is logistic regression analysis with secondary data collection process. The results of the study show that simultaneously the variables gender diversity, expertise diversity, CEO duality and board size affect financial distress. Partially, gender diversity and CEO duality variables have no effect on financial distress. Meanwhile, the expertise diversity and board size variables have a negative effect on financial distress.